Treatments for COVID-19 and acute respiratory infections are associated with gender and comorbidities in an Italian online survey - Marco Leonti; Cristina Mollica; Sara Spadaccini; Laura Casu (PLoS ONE, 2026)
Ministries of health need to know and understand factors affecting medical treatment choices of population subgroups, to tailor official recommendations. This study aimed to identify, quantify and compare treatments used by patients with an acute respiratory infection with and without COVID-19 during the first year of the pandemic by accounting for important factors potentially affecting treatment outcomes. With an online questionnaire, retrospective information on treatments used during events of acute respiratory infections were gathered in Italy. Logistic regression was used to detect significant associations between treatments and a set of variables including socio-demographic data, comorbidities and risk factors. We explored differences in treatments used by subjects who developed symptoms of an acute respiratory infection, with and without COVID-19. Women generally took more treatments than men for both, common acute respiratory infections and COVID-19, although, for the latter condition the gender difference in the average number of treatments was smaller. Painkillers (incl. NSAIDs) followed by antibiotics were the most frequently used drugs by both disease groups while the use of macrolide antibiotics and steroids were typical for the COVID group. Logistic regression models for COVID-19 treatments showed significant positive associations between women and the use of food supplements, depression severity and the use of ibuprofen, as well as between both, age class 50−64 and cardiovascular pre-conditions with macrolide antibiotics. COVID-19 patients were largely following official recommendations issued by the Italian Ministry of Health, using less complementary and alternative medicines when compared to common acute respiratory infections. Particularly, official recommendations suggesting the use of allegedly anti-inflammatory macrolide antibiotics for COVID-19 seem to have been followed for patients with cardiovascular pre-conditions. Considering that macrolide antibiotics augment the risk for cardiovascular death and that cardiovascular diseases are known to be a risk factor for COVID-19 related death, treating COVID-19 patients with macrolide antibiotics was probably not a great idea.